Decreased grain size1, a C3HC4-type RING protein, influences grain size in rice (Oryza sativa L.) - Xingjie Zhu; Shengzhong Zhang; Yaping Chen; Changlin Mou; Yunshuai Huang; Xi Liu; Jingli Ji; Jiangfeng Yu; Qixian Hao; Chunyan Yang; Mengying Cai; Thanhliem Nguyen; et al. (My University, 2021)
Decreased grain size1, a C3HC4-type RING protein, influences grain size in rice (Oryza sativa L.)
Keywords: Protein RING; Kích thước hạt lúa; Di truyền phân tử